CHARACTERISTICS OF LYMPH NODE METASTASIS IN STOMACH CANCER ADJUSTED BY LAPAROSCOPIC SURGERY AT PEOPLE'S HOSPITAL 115 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of lymph node metastasis in gastric cancer patients treated with laparoscopic surgery at 115 People’s Hospital.Subjects and Methods: This was a retrospective, descriptive case series study. All patients who underwent laparoscopic gastrectomy for gastric cancer at the Department of General Surgery, 115 People’s Hospital, from January 2020 to December 2024.Results: A total of 144 patients underwent laparoscopic gastrectomy with D2 lymph node dissection for gastric cancer. The mean number of retrieved lymph nodes was 22 ± 10 (range: 9–64). The mean number of metastatic lymph nodes was 3.7 (range: 0–21). The ratio of metastatic to retrieved lymph nodes was 16.7%. The mean number of metastatic lymph nodes increased with the depth of tumor invasion, and this difference was statistically significant (p < 0.001). When the tumor invaded beyond the muscularis propria, the mean number of metastatic lymph nodes was more than six per case. The overall lymph node metastasis rate was 51.9%. In early gastric cancer, the lymph node metastasis rate was 10%. In advanced gastric cancer, the rate was 66.1%. Among cases with tumor invasion beyond the serosa, the lymph node metastasis rate was as high as 83.7%.